Online Gambling In The Perspectives of Islamic Law and Criminal Law: A Critical Analysis of Current Cases In Indonesia - Romdoni, Muhamad; Ramadhani. MS, Renzyah Aulia (SEAN Institute, 2025)
In Indonesia, changes in the order of people's lives are greatly felt due to the presence of the influence of science and technology, namely the internet. Various groups of people have already gained access to this technology. Teenagers, as one of the largest users, often struggle to identify beneficial internet activities. They tend to be easily influenced by the social environment without first considering the positive and negative impacts that will be received in the future when using the internet. The technology that is currently developing is a problem in Indonesia. This is often misused by someone for online gambling games; this action is categorized as a criminal act of information and electronic transactions, as well as a criminal act of gambling. According to data from the Financial Transaction Reports and Analysis Center, the turnover of money from online gambling throughout 2023 reached IDR 327 trillion, approaching 10 % of the state budget. From an Islamic legal perspective, online gambling is declared haram because it does not bring benefits and causes a lot of harm. Meanwhile, in positive Indonesian law, online gambling is prohibited because it can lead to other crimes such as theft and fraud and has the potential to damage the common sense of perpetrators who often look for instant ways to fulfill their gambling desires. Data shows that online gambling perpetrators come from lower social strata, who are vulnerable to debt traps, fraud, and even suicide. The Indonesian government has made efforts to raise public awareness of the dangers of online gambling through various socializations. This study emphasizes the need for firm policies to minimize the negative impacts of online gambling that disturb the community.